EFEITO DO METHOPRENE NA ALIMENTAÇÃO DE Bombyx mori L., 1758 (LEPIDOPTERA, BOMBYCIDAE) - Zanlorenzi, G.; Alves, S. B.; Nakano, O. (REVISTA DE AGRICULTURA, 2015)
EFEITO DO METHOPRENE NA ALIMENTAÇÃO DE Bombyx mori L., 1758 (LEPIDOPTERA, BOMBYCIDAE)